Landscape and hydromorphological assessment of a mountain river valley after flood stage - Maria Nawieśniak-Caesar; Józef Hernik; Mateusz Strutyński (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study This paper aims to present an integrated assessment of changes in a mountain river valley after a flood. Material and methods The assessment followed the LandScape & HydroMorphological Assessment of River Valleys Method (LSHM Method). The method is intended for assessing and identifying valuable areas in river valleys and determining their development potential. The LSHM Method distinguishes three main groups of factors: hydromorphological (H), landscape (L), and integrated (I). All the factors are assessed using a 10-point scale. Results and conclusions Landscape and hydromorphological assessment with the LSHM Method facilitates identifying transformations of both the river channel and valley together with the areas interrelated with the river, and assessment of integrated river valley landscape. The integrated approach can be applied in the planning of repairs when restoring a river valley after a flood.